Optimization of Pre-Treatment Process in Spent Bleaching Earth (SBE) on The Characteristics of Pre-Treated SBE as Supplementary Cementitious Material - Christian Y. Pramono; Wahyuniarsih Sutrisno; Triwulan Triwulan; Pujo Aji (Institut Teknologi Sepuluh Nopember (ITS), 2024)
The palm oil processing industry in Indonesia has experienced significant growth,bringing both positive economic impacts and negative consequences, specificallythe generation of spent bleaching earth (SBE), a waste product of bleaching earth.Despite its potential as a substitute material for cement due to its pozzolanicproperties, challenges arise from SBE's oil content. Hence, this study introducespre-treatment methods involving extraction and calcination to optimize the use ofSBE, referred to as Pre-treated Spent Bleaching Earth (PSBE). This research aimsto analyze the optimized PSBE material through the optimization of the pretreatment process in the usage of mortar. The optimized PSBE is compared toanother supplementary cementitious material, which is fly ash to see theperformance of optimized PSBE as supplementary cementitious material. Theperformance of the mortar was evaluated through tests including slump test,compressive strength test, and mortar hydration temperature analysis. The pretreatment process of SBE was optimized by combining extraction and calcinationmethods, which yielded the most effective results from oil content test. One of theperformance analysis results showed that the compressive strength test revealed a28-day compressive strength value of 50,22 MPa for the optimized PSBE mortar,while the fly ash mortar had a compressive strength of 37,36 MPa. In conclusion,the optimized PSBE shows promising potential as a supplementary cementitiousmaterial.